DESIGN AND IMPLEMENTATION OF A MONITORING SYSTEM FOR DVOR EQUIPMENT STATUS USING LABVIEW - Kevin Raflyfasya; Muhammad Arif Sulaiman; Havan Hakim (Journal of Airport Engineering Technology (JAET), 2026)
The Doppler VHF Omnidirectional Range (DVOR) is a critical air navigation system that provides aircraft with azimuth information based on the Doppler effect. Monitoring of DVOR transmitter status at many facilities still relies on manual inspection or direct on-site intervention. This study designed and implemented a real-time DVOR status monitoring system in LabVIEW, integrated with RS-232 serial communication, and tested it on a THALES 432 DVOR at the CNS Laboratory of Politeknik Penerbangan Indonesia Curug. The system acquires serial data, parses the 5th byte of each data frame to classify the equipment status as Normal, Warning, or Alarm, and displays the results via color-coded LED indicators and a Waveform Chart, while logging timestamped records to an Excel file. Five functional tests across all three status conditions produced results fully consistent with the DVOR RCMS reference display, confirming the system's accuracy and reliability for real-time DVOR status monitoring.